Systemic vasculitis and aneurysm formation in the Wiskott-Aldrich syndrome. Issue 5 (1st May 1999) - McCluggage, W G; Armstrong, D J; Maxwell, R J; Ellis, P K; McCluskey, D R
Abstract : A 24 year old male who suffered from the Wiskott-Aldrich syndrome developed intra-abdominal bleeding on two occasions. Radiological investigations showed aneurysmal dilatation of branches of the hepatic and superior mesenteric arteries. The second abdominal bleed necessitated laparotomy and the bleeding was localised to the kidneys. Right nephrectomy was performed and histological examination showed a necrotising vasculitis, mainly involving medium and small sized renal blood vessels. Steroids, immunosuppressive treatment, and control of blood pressure resulted in resolution of the vasculitic process and prevented further haemorrhage. Vasculitis and aneurysm formation are rarely described complications of Wiskott-Aldrich syndrome and may account for the life threatening haemorrhage which occurs in this condition.